Bioelectrical impedance modelling of gentamicin pharmacokinetic parameters. - Zarowitz, B J (1989)
1. Bioelectrical impedance analysis was used to develop descriptive models of gentamicin pharmacokinetic parameters in 30 adult in-patients receiving therapy with gentamicin. 2. Serial blood samples obtained from each subject at steady state were analyzed and used to derive gentamicin pharmacokinetic parameters. 3. Multiple regression equations were developed for clearance, elimination rate constant and volume of distribution at steady state and were all statistically significant at P less than 0.05. 4. Clinical validation of this innovative technique is warranted before clinical use is recommended.